Assessment essentials planning, implementing, and improving assessment in higher education - Banta, Trudy W.; Palomba, Catherine A. 1943- (Jossey-Bass higher and adult education series., 2015)
In this thoroughly revised edition of Assessment Essentials, the bestselling text on outcomes assessment in higher education, you will find, in a familiar framework, nearly all new material, examples from more than 100 campuses, and indispensable descriptions of direct and indirect assessment methods that have helped to educate faculty, staff, and students about assessment. Leading authorities Trudy Banta and Catherine Palomba draw on research, standards, and best practices to address the timeliest issues in higher education accountability. This edition includes information on the use of electronic portfolios, rubrics and course-embedded assessment, assessment in student affairs, and how to assess institutional effectiveness. -- from back cover.